Vanishing Bronchus After Lung Transplantation: The Role of Sequential Airway Dilatations - Alraiyes, Abdul Hamid (Ochsner J, 2017)
BACKGROUND: Airway complications after lung transplant play an important role in patient survival. Early recognition and treatment of these complications are necessary to help ensure that patients who receive lung transplants have good outcomes. CASE REPORT: A 61-year-old female with a history of pulmonary venous occlusive disease presented to our hospital for a double-lung transplant. Her postoperative course was complicated by severe primary graft dysfunction. Airway examination showed significant mucosal ischemia distal to the anastomosis bilaterally with diffuse narrowing of all distal bronchial segments. Repeat bronchoscopies with debridement of necrotic material and balloon dilatation of stenotic airways were performed to maintain airway patency. CONCLUSION: Post–lung transplant airway necrosis and stenosis mandate early identification and treatment. Repetitive bronchoscopies with sequential balloon dilatations are mandatory to prevent future airway stenosis and airway vanishing.